Satellite-Based Urban Tree Cover Estimation System for Smart City Applications - Soto-Gomez, J; Adasme-Soto, P; Zamorano-Illanes, R (Institute of Electrical and Electronics Engineers Inc., 2023)
This research proposes to obtain, process, analyze and respond to problems at the municipal level on urban public tree cadasters for those public entities that do not have access to satellite information. A total of 28,498 public trees were obtained, of which the maximum concentrations were between 3000 to 4000 trees per km2 and the minimum between 15 to 500 trees per km2 located in the periphery and zone within the commune respectively. Satellite images provide relevant information in real time to be collected in communities and municipalities. The remote sensing used in these systems is reflected in obtaining vegetation indices that with only the use of visible spectrum bands provide crucial information about the tree quality of the study area, deficiencies and continuous improvements. This under the concepts of smart cities, in detail smart environment contribute to the management and sustainability of natural resources, providing technological solutions to monitor, analyze and optimize the use of natural resources, as well as to mitigate the negative impacts on the environment. © 2023 IEEE.